Evaluation of implant primary stability using different drilling protocols: an in vitro study - Orak, Batur; Akgul, Mehmet; Akdogan, Tuncer; Kahraman, Onur Evren (Bmc, 2025)
Background Implant surgery in the maxilla, particularly in regions with D3-D4 bone quality, poses significant challenges due to the low-density nature of the bone. In such cases, clinicians often need to deviate from standard drilling protocols recommended by implant manufacturers to optimize primary stability. These modifications may include omitting the use of a countersink drill or ending the osteotomy preparation one step earlier, based on the clinical judgement of the operator. However, there is a lack of in vitro data quantifying how these tailored surgical modifications affect implant primary stability in low-density bone. This study aimed to investigate the biomechanical impact of different drilling techniques on the primary stability of dental implants placed in D3-D4 type bone conditions. Methods An in vitro experimental study was conducted using bovine costal bone specimens resembling D3-D4 bone quality. A total of 21 Straumann BLT implants (4.1 mm x 10 mm) were placed using three drilling protocols: undersized drilling (n = 7), standard drilling (n = 7), and countersinking (n = 7). Primary stability was assessed via insertion torque (IT), removal torque (RT), and resonance frequency analysis (RFA) using the Ostell Beacon device. Statistical analysis was performed using the Kruskal-Wallis test followed by Dunn-Bonferroni post hoc tests. Significance was set at p < 0.05. Results The undersized and standard drilling groups showed significantly higher median insertion torque (20.0 Ncm and 18.0 Ncm, respectively) compared to the countersinking group (8.0 Ncm) (p < 0.05). Similarly, removal torque values were significantly greater in the undersized and standard drilling groups (27.0 Ncm each) than in the countersinking group (9.0 Ncm) (p < 0.05). Median ISQ values were highest in the undersized drilling group (77.0), followed by the standard drilling(75.0) and countersinking (69.0) groups. The difference between the undersized drilling and countersinking groups was statistically significant (p < 0.05). Conclusions In low-density bone models simulating D3-D4 bone, the use of a countersinking drill resulted in significantly reduced primary stability compared to standard and undersized drilling techniques. Undersized drilling proved more effective in enhancing implant stability when using tapered implants under low-density bone conditions.
Keywords: Dental implant; Primary stability; Undersized drilling; Countersinking; Low-density bone